Audit Expectation Gap and Decision Performance of Iranian Loan Officers - Noghondari, Amirhossein Taebi (2007)
External users of financial statements such as bank loan officers may have a greater reliance on audited financial statements in their decision-making due to their higher expectation of auditors' role and responsibility as compared to what is prescribed in statutes and thus, giving rise to an audit expectation gap. The existence of an audit expectation gap may cause loan officers to make poorer assessment of the credit worthiness of loan applicants that may result in their banks experiencing higher non-performing loans. This study proposes to examine the effects of individual factors on the extent of audit expectation gap and whether audit expectation gap would adversely affect loan officer decision performance. This study hypothesises that three individual factors, level of accounting qualification, accounting experience and occupation experience, to affect loan officer's perception of the role of audit and the reliability of the audited financial statements. A questionnaire was designed based on measures used in previous studies to evaluate the extent of the audit expectation gap with respect to perceived auditors' responsibility, reliability and decision-usefulness of audit financial statements. Based on the feedback of senior bank mangers of Iranian banks, this study used four indicators to measure the decision performance of loan officers, and the indicators were a) the percentage of non-performing loans, including bad and doubtful loans, b) the percentage of loans that failed to repay in the first 3 installments, c) the percentage of loans that failed to repay in more than 3 installments and, d) the percentage of loans rejected by loan officer's supervisor. Out of the1 13 questionnaires that were distributed to loan officers at the main branches of the five biggest commercial banks in Iran (Melli, Mellat, Saderat, Tejarat and Sepah), 11 1 questionnaires were completed and returned. Linear and multiple regression analyses indicate that accounting qualification and accounting experience have a significant and negative relationship with audit expectation gap. However, there is no significant relationship between occupational experience and audit expectation gap, but the direction of the relationship is as expected. Except for the rejected loans indicator, the results for all the other three performance indicators indicate significant and negative relationships between the loan officers' decision performance and the extent of the audit expectation gap.